ANALYSIS OF SERVICE QUALITY TOWARDS PATIENT LOYALTY WITH PATIENT SATISFACTION AS AN INTERVENING VARIABLE (SURVEY STUDY AT HERMINA MANADO HOSPITAL) - Thungari, Grace Imelda; Yuliaty, Farida; Rasyid, Renaldi Prasetya Nagar; Kosasih, Kosasih; Nugroho, Taufan (HEARTY, 2026)
The quality of health services as the most important indicator for hospitals. Optimizing service quality, building a positive hospital image, and providing supporting health service facilities are parts that marketers need to consider in order to build patient loyalty by increasing hospital patient satisfaction. This study aims to analyze the quality of health services, patient satisfaction and patient loyalty at Hermina Manado Hospital. This study uses a quantitative approach. The sample in this study amounted to 100 respondents. The data analysis used is descriptive analysis and verification analysis using path analysis. The results of the descriptive analysis of the quality of health services, patient satisfaction and patient loyalty of respondents gave a good assessment, there were still some shortcomings that must be considered for improvement. While the results of the verification study, the path analysis model showed that the path coefficient value between variables was positive and the path coefficient value of the indirect influence was greater than the direct influence (62.4%> 52.0%), meaning that the patient satisfaction variable as an intervening variable was able to mediate the health service quality variable with the patient loyalty variable.